The Model Trainning Program for Overseas Dhammaduta Bhikkus Class 26 Dhammaduta College and The Strategy to Prevent Speading Coronavirus Disease Starting in (Covid 2019) - Aggatejo (Phromsena), Phrakhrudhammathon Waradecha (Mahachula Academic Journal, 2023)
The qualitative research aimed (1) To Study The Model Training Program for Overseas Dhammaduta Bhikkhus of The Dhammaduta college which organizes a training program in the area of ​​Phra Nakhon Sri Ayutthaya and Phetchabun provinces (2) To Study national strategy according to the resolution of the board of directors Sangha association in Prevent Speading Coronavirus Disease Starring in 2019, Collecting data from monks who attended the training Program for Overseas Dhammaduta Bhikkhus Version 26 in Year B.E. 2564, In which monks attended the training in field activities Number of 110 Persons. Eeveryone involved with The Training Program have followed the strategy to prevent speading coronavirus disease staring in 2019 according to the resolution of the government and strictly according to the resolutions of the Sangha Council members strictly throughout the start of the activity The Model Training Program for Overseas Dhammaduta Bhikkhus. The results showed that The Model Training Program This is the training of monks.in The Model Training Program for Overseas Dhammaduta Bhikkhus, which is the selection method, screening, qualified person, both in terms of knowledge, skills, to the extent that it can represent , in propagating Buddhism, to spread throughout both domestic and international, especially America and Europe, is getting attention from foreigners in Buddhism, is the development of the brain, on the dissemination, Not just a Dhammaduta, But if it is still a person who has developed to be intelligent, experienced both theoretical and practical, can bring knowledge, skills and experience, to develop oneself and the public, both at home and abroad.